A search for prompt lepton-jets in pp collisions at root s=8 TeV with the ATLAS detector - Onofre, A. (2016)
A search is presented for a new, light boson with a mass of about 1 GeV and decaying promptly to jets of collimated electrons and/or muons (lepton-jets). The analysis is performed with 20.3 fb−1 of data collected by the ATLAS detector at the Large Hadron Collider in proton-proton collisions at a centre-of-mass energy of 8 TeV. Events are required to contain at least two lepton-jets. This study finds no statistically significant deviation from predictions of the Standard Model and places 95% confidence-level upper limits on the contribution of new phenomena beyond the SM, incuding SUSY-portal and Higgs-portal models, on the number of events with lepton-jets.